Dynamically close galaxy pairs from the unWISE survey - Chishala, Josephine; De Propris, Roberto; Povic, Mirjana (EDP Sciences, 2026)
Context
Galaxy mergers are expected to have a profound influence on the star formation histories of galaxies. It is generally expected that mergers are the main drivers of galaxy mass growth through the accretion of mass and the triggering of new star formation episodes, while the shocks and torques induced by the merger may drive gas and dust to central supermassive black holes and fuel active galactic nucleus (AGN) activity and produce both positive and negative feedback.
Aims
We test whether a merger-AGN-star formation connection exists by selecting samples of galaxy pairs of stellar masses log(M/M⊙)∼10.2 and ∼11.4 within redshift z < 0.25 at various projected separation and velocity differences in an increasing order, and would therefore have a decreasing probability of being truly bound and interacting.
Methods
We identified galaxies in close pairs and then measured their star formation rates (SFRs; via their NUV − r colours) and the degree of AGN activity (from X-rays, radio emission at 20 cm, WISE infrared colours, and emission line ratios) as a function of their projected separation and velocity difference.
Results
We find only weak evidence that galaxies in pairs have higher SFRs as galaxies become closer in projected and velocity separation. This trend occurs for pairs at closest separation of rp < 20 kpc and ΔV < 500 km/s. Similarly, we observe no strong evidence that AGNs are more common for galaxies in closer pairs, irrespective of the method used to detect AGNs.
Conclusions
For this sample, we did not find any clear evidence that mergers and interactions may play a significant role in triggering star formation and AGN activity, opposite to expectations from theoretical models invoking feedback episodes. Secular processes may be more important, although this may depend on the selection of galaxies and indicators for star formation and AGN activity.